New evidence of heterogeneous bank interest rate pass-through in the euro area - Dominik Bernhofer; Till van Treeck (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2011)
We analyse the bank interest rate pass-through in the euro area for the period 1999:1 - 2009:11, relating market interest rates to bank retail rates of comparable maturities. We first estimate single equation error correction models for seven interest rate categories and ten euro area countries and find that the interest rate pass-through displays substantial heterogeneity especially in the short run, but also in the long run. We then apply the pooled mean group estimator (PMGE) advanced by Pesaran et al. (1999), allowing for country-specific interest rate pass-through in the short run, while constraining the long-run pass-through to be homogeneous across countries. We find significant evidence of substantial heterogeneity in the short-run passthrough. Finally, we conduct sub-sample analysis and conclude that the degree of heterogeneity and the overall efficiency of the interest rate pass-through have not improved in the second half of the existence of the European Monetary Union.
urn:nbn:de:101:1-201202285269
Keywords: 330; Geldpolitische Transmission; Schätzung; Eurozone